Creation of an IEC 62304 compliant software development plan. Issue 11 (17th October 2016) - Rust, Peter; Flood, Derek; McCaffery, Fergal
Abstract: Organizations engaged in medical device software development are required to demonstrate compliance with a set of medical device standards and regulations before the device can be marketed. One such standard IEC 62304, Medical Device Software—Software Life Cycle Processes, defines the processes that are required in order to develop safe software. Demonstrating compliance with IEC 62304 can be problematic for organizations that are new to or have limited experience in the domain. The standard defines what processes must be carried out but does not state how. In a review of a number of such organizations, it was found that the development of a software development plan proved to be a difficult task. In this work we have created a software development plan template to assist organizations with this arduous task. The software development plan template will be validated with these organizations as part of the future work. Abstract : During an evaluation of 2 organizations entering the medical device domain, it was found that one of the critical issues experienced was the creation of a software development plan. To address this issue, we present an IEC 62304 compliant software development plan template which incorporates all of the requirements of the IEC 62304 standard. This template represents the first artifact in the development of a roadmap for the implementation of IEC 62304.